Phosphorylation of Threonine 175 Tau in the Induction of Tau Pathology in Amyotrophic Lateral Sclerosis—Frontotemporal Spectrum Disorder (ALS-FTSD). A Review - Moszczynski, Alexander J.; Hintermayer, Matthew A.; Strong, Michael J. (Frontiers in Neuroscience, 2018)
Approximately 50 to 60% of all patients with amyotrophic lateral sclerosis (ALS) will develop a deficit of frontotemporal function, ranging from frontotemporal dementia (FTD) to one or more deficits of neuropsychological, speech or language function which are collectively known as the frontotemporal spectrum disorders of ALS (ALS-FTSD). While the neuropathology underlying these disorders is most consistent with a widespread alteration in the metabolism of transactive response DNA-binding protein 43 (TDP-43), in both ALS with cognitive impairment (ALSci) and ALS with FTD (ALS-FTD; also known as MND-FTD) there is evidence for alterations in the metabolism of the microtubule associated protein tau. This alteration in tau metabolism is characterized by pathological phosphorylation at residue Thr175 (pThr175 tau) which in vitro is associated with activation of GSK3beta (pTyr216GSK3beta), phosphorylation of Thr231tau, and the formation of cytoplasmic inclusions with increased rates of cell death. This putative pathway of pThr175 induction of pThr231 and the formation of pathogenic tau inclusions has been recently shown to span a broad range of tauopathies, including chronic traumatic encephalopathy (CTE) and CTE in association with ALS (CTE-ALS). This pathway can be experimentally triggered through a moderate traumatic brain injury, suggesting that it is a primary neuropathological event and not secondary to a more widespread neuronal dysfunction. In this review, we discuss the neuropathological underpinnings of the postulate that ALS is associated with a tauopathy which manifests as a FTSD, and examine possible mechanisms by which phosphorylation at Thr175tau is induced. We hypothesize that this might lead to an unfolding of the hairpin structure of tau, activation of GSK3beta and pathological tau fibril formation through the induction of cis-Thr231 tau conformers. A potential role of TDP-43 acting synergistically with pathological tau metabolism is proposed.